Measurement procedures affect the interpretation of metatarsophalangeal joint function during accelerated sprinting - Smith, G.; Lake, M.; Lees, A.; Worsfold, P. (Journal of Sports Sciences, 2012)
The metatarsophalangeal joint (MPJ) is a significant absorber of energy in sprinting. This study examined the influence of MPJ axis choice and filter cut-off frequency on kinetic variables describing MPJ function during accelerated sprinting. Eight trained sprinters performed maximal sprints along a runway. Three-dimensional high-speed (1000 Hz) kinematic and kinetic data were collected at the 20 m point. Three axis definitions for the five MPJs were compared. MPJ moments, powers and energies were calculated using different filter cut-off frequencies. The more anatomically appropriate dual axis resulted in less energy absorbed at the MPJ compared to the oblique axis which also absorbed less energy compared to the perpendicular axis. Furthermore, a low cut-off frequency (8 Hz) substantially underestimated MPJ kinematics, kinetics and the energy absorbed at the joint and lowered the estimate of energy production during push-off. It is concluded that a better understanding of MPJ function during sprinting would be obtained by using an oblique or anatomically appropriate representation of the joint together with appropriate kinematic data sampling and filtering so that high frequency movement characteristics are retained.